Microbiological Evaluation of Blepharitis: A Case-Controlled Study - Sourat Mudassar; Abida Bano; Maryam Shahid; Farah Asghar; Fadia Waheed; Numan Javed (BioScientific Review, 2024)
Background. Blepharitis is a chronic inflammatory eyelid infection. The current study was designed to check the association of normal bacterial flora of normal eyelids with the potential pathogenic bacteria of blepharitis infected eyelids of blepharitis patients.Methodology. A total of (n=50) blepharitis patients were recruited for this study. Then, 100 swab samples were taken from these patients. Sample distribution indicated that 50 swab samples were taken from infected eyelids and 50 from the uninfected part of eyelids of blepharitis patient. Bacterial flora was characterized in these samples through different biochemical tests and antibiotic resistance was checked by using the Kirby Bauer (KB) method.Results. A total of 52 bacterial strains were isolated from 50 infected swab samples of 50 blepharitis patients including Staphylococcus aureus 31/52 (60%), Staphylococcus epidermidis 7/52 (13%), Klebsiella spp. 6/52 (11%), E. coli 2/52 (4%), Acinetobacter spp. 2/52 (4%), Enterobacter spp. 1/52 (2%), Serratia marcescens 1/52 (2%), Shigella spp. 1/52 (2%) and Bacillus cereus 1/52 (2%). Further, 48 bacterial strains were isolated from uninfected swab samples of 50 blepharitis patients including Staphylococcus epidermidis 24/48 (50%), Staphylococcus aureus 22/48 (42%), Klebsiella spp. 1/48 (2%), Enterobacter spp. 1/48 (2%), Serratia spp. 1/48 (2%), and Acinetobacter spp. 1/48 (2%). All Gram-positive bacteria isolated from both infected and uninfected eyelids were found to be sensitive to vancomycin antibiotics. The percentage of methicillin-resistant Staphylococcus aureus (MRSA) was 21% among the bacterial isolates obtained from infected eyelids. While, its percentage was 18.7% in the bacterial isolates obtained from the uninfected eyelids of the patients. Hence, the percentage of MRSA was higher in the infected eyelids of blepharitis patients as compared to their uninfected eyelids.Conclusion. The identification of pathogens involved in blepharitis and performing their antibiotic susceptibility test (AST) are important steps in reducing bacterial resistance for blepharitis treatment.